Does Hunger Contribute to Socioeconomic Gradients in Behavior? - Nettle, Daniel (Frontiers in Psychology, 2017)
Recent research has uncovered many examples of socioeconomic gradients in behaviour and psychological states. As yet there is no theoretical consensus on the nature of the causal processes that produce these gradients. Here, I present the hunger hypothesis, namely the claim that part of the reason that people of lower socioeconomic position behave and feel as they do is that they are relatively often hungry. The hunger hypothesis applies in particular to impulsivity-hyperactivity, irritability-aggression, anxiety, and persistent narcotic use, all of which have been found to show socioeconomic gradients. I review multiple lines of evidence showing that hunger produces strong increases in these outcomes. I also review the literatures on food insufficiency and food insecurity to show that, within affluent societies, the poor experience a substantial burden of hunger, despite obtaining sufficient or excess calories on average. This leads to the distinctive prediction that hunger is an important mediator of the relationships between socioeconomic variables and the behavioural/psychological outcomes. This approach has a number of far-reaching implications, not least that some behavioural and psychological differences between social groups, though persistent under current economic arrangements, are potentially highly reversible with changes to the distribution of financial resources and food.